Plant Growth of Beetroots (Beta vulgaris L.) with Nitrogen Supply at Suboptimal Elevations in a Tropical Region - S.M. Sitompul; Muhammad Roviq; Ariesta Yudha; Stepani Astrid Khesia; Nathania Julia Avyneysa; Yolanda Yolanda (AGRIVITA, Journal of Agricultural Science, 2020)
The present study was designed to study the possibility of beetroots to be cultivated at suboptimal elevations in the tropics. Four pot experiments were conducted in the field each at 1700, 850, 520 and 320 m asl (above sea level) in the region of Malang, East Java. A randomized block design with four replicates was used to impose the treatment of nitrogen (N) fertilizer consisting of 0, 0.4, 0.8 and 1.2 g N/plant (~ 0, 100, 200 and 300 kg N/ha). In the experiments at the elevation of 1700 m and 320 m asl, the treatment of 0 and 80 g chicken manure per plant (~ 0 and 20 t/ha) was involved. The treatment of 0 and 0.6 g P2O5 and 0 and 0.8 g K2O per plant was involved in the experiment at 850 m and 520 m asl respectively. Plant growth (total dry weight, leaf area and leaf number) was observed on day 20, 40, 60 and 90 after sowing by destructive plant samplings. In the present paper, data were reorganized to analyze the effect of elevation and N fertilizer on plant growth with the elevation as the main factor and N fertilizer as the sub factor.